Reliability and cost efficiency analysis for deep space habitat network based on Nash bargaining solution - Zi-jing CHENG; Jun-nan ZHAO; Yu-wen CUI; Le-yi SHI (Tongxin xuebao)
Focusing on the deep space habitat network requirements of high reliability and expensive links,two impact factors to the network performance were regarded as a multi-objective optimization problem,which were network reliability and cost efficiency model,and the relations between the two factors were formalized.Thereafter,the Nash model of cooperative game was used to make a fairness compromise to the network reliability and cost efficiency,and the Nash bargaining solution set was acquired through the Matlab platform with CVX.Further,through changing the threat value dynamically and performing the repeated game,the Pareto optimal solution could be obtained which can ensure the fairness of reliability and cost efficiency simultaneously.Finally,the Nash bargaining method was applied to a typical deep space habitat network topology,and described in detail how to set up the link numbers and link capacity in order to reduce the cost when the network traffic and the link capacity were given.The proposed work is important for the deployment and optimization of the deep space habitat network.